Factors Affecting Patients' Acceptance of and Satisfaction with Cloud-Based Telehealth for Chronic Disease Management: A Case Study in the Workplace - Su, Yung-Yu; Huang, Su-Tsai; Wu, Ying-Hsun; Chen, Chun-Min (Applied Clinical Informatics, 2020)
Objective Understanding patients' acceptance of and satisfaction with telehealth use is important for workplace health promotion. In this study, we used a questionnaire to measure patients' usage behavior and satisfaction with cloud-based telehealth services in the workplace. We empirically investigated the factors that influence patients' usage and satisfaction based on data collected from 101 participants.Methods As its main research framework, this study utilized a revised version of the technology acceptance model 2 that was based on the telehealth services provided for chronic disease management. Through integrating a cross-sectional research design with an author-developed structured questionnaire that was assessed using reliability and validity tests, an anonymous survey was conducted on selected participants. The proposed research model and hypotheses were validated through path analysis using SPSS.Results We found that users believe telehealth services can promote their workplace health management; that job relevance, result demonstrability, and perceived ease of use (PEOU) positively affect the perceived usefulness (PU), which implies that cognitive instrumental processes have the most significant impact on the PU of cloud-based telehealth; and that both PEOU and PU positively affect the intention to use (IU), but PU has a bigger influence than PEOU on users' intentions to continue using telehealth. In particular, the IU and actual usage behavior were critical to the patients' satisfaction with telehealth services.Conclusion This research contributes to the rapid developing field of technology acceptance research by examining workplace telemedicine engagement. Our results will provide researchers with useful advice and a user-centered strategy for promoting workplace health management, which benefits both health care providers and corporate managers.
Keywords: satisfaction; telehealth; chronic disease management; technology acceptance model 2